Response: Lynch, J. and Porcellato, A. (2020) The Case for an Aviation English Screening Tool for US Flight Schools The Especialist 41, 4 - Response - Latitude Team, Latitude Aviation English Services (The ESPecialist, 2022)
We enjoyed reading your paper, The Case for an Aviation English Screening Tool for US Flight Schools, in the Especialist. Not only is it encouraging to see more focus on this area which has been given scant attention over the years, but we were interested to see Checkpoint discussed for the first time. It is gratifying that you recognise Checkpoint’s strengths, as well as setting out areas which you believe could be improved.